2003
DOI: 10.1055/s-2003-41566
|View full text |Cite
|
Sign up to set email alerts
|

Randomisierte Studie zur Akupunktur im Vergleich mit konventioneller Massage und Schein-Laserakupunktur in der Behandlung chronischer HWS-Beschwerden - Bewegungsanalyse

Abstract: The results of the study indicate that acupuncture is superior to conventional massage for improving active range of motion in patients with chronic neck pain. Because of its positive effects, its acceptance among patients and the lack of severe side effects, acupuncture can be recommended for the treatment of chronic neck pain, although there was no significant difference in results between "sham" laser acupuncture and acupuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In general, sham acupuncture can be divided into two categories: non-penetrating and penetrating sham acupuncture, which is determined by whether the needle penetrates the skin during the intervention. According to the literature, there are four types of non-penetrating sham acupuncture in use: 1) skin touch on standard points or non-points [24,25], 2) blunt telescoping sham needle [26,27], 3) transcutaneous electrical stimulation [28], and 4) sham laser acupuncture [29,30]. It is reported the non-penetrating sham acupuncture has been applied as a placebo in numerous trials; however, it was also found that 40% of the subjects in these trials could distinguish the sham acupuncture from the real treatment [31], breaking the blind concealment.…”
Section: Discussionmentioning
confidence: 99%
“…In general, sham acupuncture can be divided into two categories: non-penetrating and penetrating sham acupuncture, which is determined by whether the needle penetrates the skin during the intervention. According to the literature, there are four types of non-penetrating sham acupuncture in use: 1) skin touch on standard points or non-points [24,25], 2) blunt telescoping sham needle [26,27], 3) transcutaneous electrical stimulation [28], and 4) sham laser acupuncture [29,30]. It is reported the non-penetrating sham acupuncture has been applied as a placebo in numerous trials; however, it was also found that 40% of the subjects in these trials could distinguish the sham acupuncture from the real treatment [31], breaking the blind concealment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the use of placebos for control purposes in said research is essential to assess the real effectiveness of an intervention (7) . However, given the absence of a proper placebo method in acupuncture to be used as control in clinical studies, researchers have applied diverse comparative methods such as TENS (8) , laser (9) , superficial acupuncture (10)(11) , the stimulation of points which are close to acupuncture points (12,10) or a combination of the latter (13)(14)(15) , thus raising questions regarding the internal and external validity of said studies. Developing a placebo acupuncture needle as a control mechanism for clinical research purposes has been a historical challenge in this area of knowledge.…”
Section: Introductionmentioning
confidence: 99%